Gear Fault Recognition based on Local Detail Spectrum - Yan Hao; Xiao Han (Jixie chuandong)
Unlike the normal recurrence quantification analysis（ RQA） which pay attention to the distribution of different kinds of lines such as diagonal lines,vertical lines and horizontal lines,a new perspective to study recurrence plot（ RP） is developed and the local detail spectrum（ LDS） will be proposed as one new RQA measure. This method pay more attention to the local details of the recurrence plot. The application of LDS in gear fault signal is studied in detail. The experiment proved the better performance of LDS in the field of gear fault diagnosis.